2020
DOI: 10.3390/insects11060368
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Morphological Studies Confirm That the Classical Object of Pest Control Chilocorus kuwanae Is the Same Species as Ch. renipustulatus (Coleoptera: Coccinellidae)

Abstract: The ladybug Chilocorus kuwanae, which was described in Japan, has been used for biological control of pests for 100 years. Chilocorus kuwanae was recently synonymized with Ch. renipustulatus described in Europe. The synonymy was based on the examination of few specimens. Our aim is to verify this synonymy. We studied all characters previously used to distinguish these taxa: eight metric and nine qualitative characters. Examination of 107 specimens from Japan and Sakhalin and 174 specimens from Europe showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our data have shown that the populations of five of these species still exist in the region ( Table 3 ). Besides that, specimens of C. kuwanae (Silvestri, 1909) introduced from Japan were released [ 7 ], but we have revealed that C. kuwanae (Silvestri, 1909) is the junior synonym of C. renipustulatus (Scriba, 1790), which is the native element of the ladybird fauna at the Black Sea coast of Russia [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data have shown that the populations of five of these species still exist in the region ( Table 3 ). Besides that, specimens of C. kuwanae (Silvestri, 1909) introduced from Japan were released [ 7 ], but we have revealed that C. kuwanae (Silvestri, 1909) is the junior synonym of C. renipustulatus (Scriba, 1790), which is the native element of the ladybird fauna at the Black Sea coast of Russia [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The author follows the classical rule [40,41], which was recently (successfully) tested by Bie ńkowski, Orlova-Bienkowskaja [42]: 97% of specimens in one sample should be separable from 97% of specimens in the other sample, to qualify these samples as representing different subspecies. Amadon [40] showed that this rule is fulfilled for a metric character if the following inequalities are true:…”
Section: Criteria Of Subspeciesmentioning
confidence: 99%
“…One article stressed the importance of rigorous morphological investigations to accurately identify predatory coccinellids ( Chilocorus species) before release for classical biological control of coccids [ 4 ]. The authors found that Chilocorus kuwanae Silvestri and Chilocorus renipustulatus (Scriba) were the same species.…”
mentioning
confidence: 99%
“…kuwanae in Europe and the Caucasus did not represent classical biological control, since the same species (misidentified as C . renipustulatus ) were native to these regions [ 4 ].…”
mentioning
confidence: 99%